CURRENT MANAGEMENT TRENDS IN AGRICULTURAL PRODUCTION - Reva, Svitlana (SWorld-Ger Conference proceedings, 2024)
The article examines the main challenges facing the agricultural sector in the context of globalization, climate change, and increasing efficiency requirements. The role of digital technologies, such as precision agriculture, drones and the Internet of Th